2019
DOI: 10.1016/s2542-5196(19)30047-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between pregnancy loss and ambient PM2·5 using survey data in Africa: a longitudinal case-control study, 1998–2016

Abstract: Background Increasing evidence from epidemiological studies suggests that maternal exposure to ambient PM 2•5 can increase the risk of pregnancy loss. However, no studies have been done in low-income countries such as those in Africa, which have the highest incidences of pregnancy loss. In this study, we aimed to analyse the association between PM 2•5 and pregnancy loss, including miscarriage and stillbirth. Methods This self-compared case control study collected data on mothers who reported at least two birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…Many toxic components, such as the heavy metals and PAHs are present in PM, which are capable of exerting developmental toxicities (Shankar et al, 2019;Zhao et al, 2020). Epidemiological studies revealed that developmental exposure to PM resulted in increased risk of asthma (Kravitz-Wirtz et al, 2018), decreased airway antimicrobial activity (Zhang et al, 2019), low birth weight (Wang et al, 2019b), and pregnancy loss (Xue et al, 2019).…”
Section: A B Cmentioning
confidence: 99%
“…Many toxic components, such as the heavy metals and PAHs are present in PM, which are capable of exerting developmental toxicities (Shankar et al, 2019;Zhao et al, 2020). Epidemiological studies revealed that developmental exposure to PM resulted in increased risk of asthma (Kravitz-Wirtz et al, 2018), decreased airway antimicrobial activity (Zhang et al, 2019), low birth weight (Wang et al, 2019b), and pregnancy loss (Xue et al, 2019).…”
Section: A B Cmentioning
confidence: 99%
“…The evidence in the existing reviews on ambient air pollution and/or temperature and birth outcomes [19][20][21][22][23][24][25]30,31,37] is heavily based on studies for high income countries while acknowledging lack of evidence from low-and middle-income countries (LMICs). Conceivably, this may be due to generally limited environmental health researches in developing countries such as Africa [38,39] and even in some East Asian and Pacific Island countries. Despite their limitations, analytical cross-sectional and ecological studies provide exploratory information to generate hypotheses for possible links between environmental factors and disease outcomes [18,40].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, one conclusion made by Rees et al [49] is that "we are not only potentially underestimating the impact we might also not know how bad it is until it is too late". Results from recent studies [38,39,50] using Demographic Health Survey (DHS) data and gridded satellite-based estimates of PM 2.5 across Africa indicate strong significant associations. For instance, exposure to early-life carbonaceous PM 2.5 increased the odds of neonatal mortality (OR: 1.22; 95% CI: 1.11-1.35) on the log PM 2.5 exposure level [38], higher odds for pregnancy loss cases with 26.64 µg/m 3 exposure than the control with 25.69 µg/m 3 exposure level (1.22; 1.107-1.137), and this included miscarriage (1.125; 1.109-1.142) and stillbirth (1.094; 1.05-1.38) per 10 µg/m 3 increase in PM 2.5 exposure [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Tao Xue and colleagues 7 is the first large study to examine the association between fine particles and pregnancy loss across 33 African countries. The authors took advantage of a large multicountry sample of 42 952 women with selfreported pregnancy losses (1998-2016), who also had a successful pregnancy before or after the index loss.…”
mentioning
confidence: 99%